2023
DOI: 10.3390/cancers15041212
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons in Metastatic Colorectal Cancer: Prognostic Role of CD44 Expression

Abstract: Background: The transmembrane glycoprotein CD44, the major hyaluronan (HA) receptor, has been proven to regulate cell growth, survival, differentiation, and migration. It is therefore widely considered to be involved in carcinogenesis. Its role as a new therapeutic target in solid tumors is under evaluation in clinical trials. The prognostic value remains controversial. Here, we aimed to investigate the correlation between CD44 expression and the clinicopathological features and survival in metastatic colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Furthermore, in our recent study, high CD44 expression was significantly associated with higher proliferative activity of CRC and poor prognosis. CD44 overexpression was also associated with clinically poor prognostic features: older age, inoperable disease, stage IV at diagnosis, mutated BRAF, and high-grade tumor [101,102]. Conversely, in a previous study, a statistically significant correlation was found between positive CD44 expression and left-sided tumors in an Egyptian population [103], which tend to be associated with a better prognosis than right-sided CRC localization [104,105].…”
Section: Prognostic Rolementioning
confidence: 64%
“…Furthermore, in our recent study, high CD44 expression was significantly associated with higher proliferative activity of CRC and poor prognosis. CD44 overexpression was also associated with clinically poor prognostic features: older age, inoperable disease, stage IV at diagnosis, mutated BRAF, and high-grade tumor [101,102]. Conversely, in a previous study, a statistically significant correlation was found between positive CD44 expression and left-sided tumors in an Egyptian population [103], which tend to be associated with a better prognosis than right-sided CRC localization [104,105].…”
Section: Prognostic Rolementioning
confidence: 64%
“…Today, anti-angiogenic treatment represents a cornerstone of mCRC patient management in both the first-and second-line settings [3][4][5][6][7][8][9][10][11][12]. Unfortunately, the real OS gain from bevacizumab, aflibercept, and ramucirumab emerged from clinical trials and reallife data is about 1.4 to 1.6 months, which is quite marginal in the clinical history of a mCRC patient [3][4][5][6][7][8][9][10][11][12]16,17,[116][117][118][119]. The same concept applies even more to the role of regorafenib in further lines of treatment [20,120].…”
Section: Discussionmentioning
confidence: 99%
“…Around 20% of patients with CRC present with metastatic spread at diagnosis, and 30% among those with early stage disease will develop metastasis during their life [2][3][4]. Thanks to the development and introduction into clinical practice of new therapeutic strategies, in the last ten years the median overall survival (OS) of metastatic colorectal cancer (mCRC) patients has reached 35 months; however, OS at five years still does not exceed 20% [5,6]. Nowadays, the standard of care for mCRC treatment is represented by first-line fluoropyrimidine-based chemotherapy, either single agent or in combination with oxaliplatin or irinotecan (doublet or triplet regimen), plus biological agents targeting either vascular endothelial growth factor (VEGF, bevacizumab) or epidermal growth factor receptor (EGFR, panitumumab or cetuximab).…”
Section: Introductionmentioning
confidence: 99%
“…The amplification or overexpression of Cyclin D1 alters cell cycle progression and leads to tumorigenesis [ 37 ]. CD44 is involved in the process of heterogeneous adhesion of tumor cells and plays a role in promoting the invasion and metastasis of tumor cells [ 38 ]. Additionally, the intracellular domain of E-cadherin interacts with β-catenin, maintaining cell adhesion [ 39 ], and it was found that in PRAME-knockdown cells, E-cadherin expression was upregulated, and N-cadherin expression was downregulated; whereas in PRAME-overexpressed cells, E-cadherin expression was decreased, and N-cadherin expression was increased.…”
Section: Discussionmentioning
confidence: 99%